actors Affecting the Constraints in Inorganic and Organic Fertilizersuse in Paddy Cultivation (Indian Journal of Extension Education, 2010)
The study was conducted in Milkipur block of Faizabad district selected purposively on 100 respondents selected through proportionate random sampling technique on the basis of holding size possessed by the paddy growers. The respondents were contacted personally for data collection. The results of the study depicted that the maximum percentage of respondents were found in age group at 37-62 years (60%), literate (73%) and belonged to backward caste (38%). The joint families were observed maximum having 5 to 12 members (55%) in their families. The land holding below one ha was observed with maximum farmers (68%). The maximum i.e. 38 per cent and 37 per cent respondents residing in pucca and mixed type houses, respectively and the agriculture was observed dominant as main occupation with 61 per cent respondent. The maximum (36%) respondents were found participated in one organization, while 33 per cent did not take participation at all in any organization. The maximum (42%) respondents were found earning the annual income of Rs. 20001 to 40000 and majority of respondents (67%) were observed in medium category (7 to 31 scores) of materials possession.’ The radio was main communication media (64%) with the paddy growers. Maximum respondents were found in medium levels of scientific orientation, economic motivation, risk orientation and value orientations with 53 per cent, 44 per cent, 72 per cent and 51 per cent, respectively. The variables like, holding size, social participation and Income, material possession and formal extension contact were found to have significant and negative relationship with constraints in balance use of inorganic fertilizers, while scientific orientation was found significantly and positively correlated. The variables like income, and material possession were found to have significant and negative correlation with constraints in organic fertilizers use, while one variable i. e., scientific orientation was found significant and positive relationship. Thus, it may be said that the above variables needs to be intervened for making further strategy regarding fertilizers use.